W. J. T. Mitchell's Core Ideas on Image and Text - Susanti, Anastasia Jessica Adinda (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2025)
This study examines the important ideas of W.J.T. Mitchell’s theories on image and text. The link between word and image has long been a topic of controversy, from Plato's differentiation between